2019
DOI: 10.1002/hyp.13402
|View full text |Cite
|
Sign up to set email alerts
|

Rill flow resistance law under equilibrium bed‐load transport conditions

Abstract: In this paper, a recently deduced flow resistance equation for open channel flow was tested under equilibrium bed‐load transport conditions in a rill. First, the flow resistance equation was deduced applying dimensional analysis and the incomplete self‐similarity condition for the flow velocity distribution. Then, the following steps were carried out for developing the analysis: (a) a relationship (Equation ) between the Γ function of the velocity profile, the rill slope, and the Froude number was calibrated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
4
14
0
Order By: Relevance
“…At present, the contribution of sediment transport to rill flow resistance has been little investigated. The study by Di Stefano, Nicosia, Pampalone, Palmeri, and Ferro (2019) based on Jiang et al’s (2018) measurements established that flow resistance increases with bed load transport, in accordance with the available results for open channel flows (e.g., Gao & Abrahams, 2004). According to Di Stefano, Nicosia, Palmeri, Pampalone, and Ferro (2019), the impact of the overall (i.e., bed load and suspended) sediment transport on the flow resistance should be significantly lower than that of the grain roughness.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…At present, the contribution of sediment transport to rill flow resistance has been little investigated. The study by Di Stefano, Nicosia, Pampalone, Palmeri, and Ferro (2019) based on Jiang et al’s (2018) measurements established that flow resistance increases with bed load transport, in accordance with the available results for open channel flows (e.g., Gao & Abrahams, 2004). According to Di Stefano, Nicosia, Palmeri, Pampalone, and Ferro (2019), the impact of the overall (i.e., bed load and suspended) sediment transport on the flow resistance should be significantly lower than that of the grain roughness.…”
Section: Discussionsupporting
confidence: 65%
“…This result is due to a “feedback mechanism” because when slope gradient increases the expected increase of flow velocity is counterbalanced by the increase of bed roughness due to a more active rill erosion process. For the rills investigated by Jiang et al (2018) the feedback mechanism was not allowed because the flow could not shape the rill channel and was only able to transport the supplied sediment particles (Di Stefano, Nicosia, Pampalone et al, 2019). The result of a slope‐independent flow velocity obtained here can be attributed to the limited number of measurements characterized by a non‐erodible bed as compared to those carried out for a mobile bed condition.…”
Section: Discussionmentioning
confidence: 99%
“…At present, limited information on the effect of sediment transport on rill flow resistance is available. Di Stefano, Nicosia, Pampalone, et al (2019) using the measurements by Jiang et al (2018) established that flow resistance increases with bed load transport, in accordance with the available results for open channel flows (Gao & Abrahams, 2004). Furthermore, the impact of the overall (i.e., bed load and suspended) sediment transport on the rill flow resistance should be significantly lower than that of the grain roughness (Di Stefano, Nicosia, Palmeri, et al, 2019).…”
Section: Discussionsupporting
confidence: 71%
“…The proposed flow resistance equation was also tested using field data collected in 104 reaches of some Calabrian gravel bed rivers (Ferro and Porto 2018b). Di Stefano et al (2019a) tested the same theoretical flow resistance equation using 35 experimental runs of Jiang et al (2018) which investigated the effect of flow discharge and slope steepness on rill sediment transport capacity. The analysis confirmed that function can be estimated using the channel slope, the Shields number, and the Froude number and that the flow resistance law allows for an accurate estimate of the friction factor f.…”
mentioning
confidence: 99%